Comparative study of survivor and nonsurvivor sepsis patients in a university hospital Estudo comparativo de pacientes sobreviventes e não sobreviventes com sepse em um hospital universitário - Aline Pâmela Vieira de Oliveira; Cristina Hueb Barata; Eddie Fernando Candido Murta; Beatriz Martins Tavares-Murta (Revista da Sociedade Brasileira de Medicina Tropical, 2008)
To determine parameters associated with the evolution of sepsis, a five-year retrospective study was conducted in a university hospital. One hundred and four consecutive sepsis patients were evaluated, of whom 55.8% were men. The mortality was 68.3% and was associated with older age (p<0.05). Chronic comorbidities and infection site were not associated with prognosis. Gram-positive bacteria were more frequently identified in survivors (p<0.05), while non-detection of the germ was associated with mortality (p<0.01). Appropriate use of antibiotics (germ sensitive to at least one drug administered) was associated with survival (p<0.0001) while inappropriate use (p<0.05) or empirical use (p<0.01) were more frequent in nonsurvivors. Leukocytosis was the main abnormality (54.8%) detected on diagnosis, from the leukocyte count. During the evolution, normal leukocyte count was associated with survival (p<0.01) and leukocytosis with mortality (p<0.05). In conclusion, mortality was associated with nondetection of the pathogen, leukocytosis during the evolution of the sepsis and inappropriate or empirical use of antimicrobials. Evidence-based treatment that is directed towards modifiable risk factors might improve the prognosis for sepsis patients. Para determinar parâmetros associados à evolução da sepse, foi realizado estudo retrospectivo de 5 anos em um hospital universitário. Foram avaliados 104 pacientes consecutivos com sepse, sendo 55,8% homens. A mortalidade foi de 68,3%, associada à idade elevada (p<0,05). Doenças crônicas associadas e sítio de infecção não relacionados ao prognóstico. Identificação de bactérias gram-positivos foi mais frequente em sobreviventes (p<0,05) e não detecção do germe foi associada à mortalidade (p<0,01). O uso apropriado de antibióticos (germe sensível a pelo menos uma droga administrada) foi associado à sobrevida (p<0,0001) enquanto uso inapropriado (p<0,05) ou empírico (p<0,01) foi mais freqüente em não sobreviventes. No diagnóstico, ...